2023
DOI: 10.1177/03635465231158099
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Trochlear Dysplasia: Normal Thresholds Vary by Measurement Technique, Landmarks, and Sex

Abstract: Background: Trochlear dysplasia is a known risk factor for patellar instability. Multiple radiographic measurements exist to assess trochlear morphology, but the optimal measurement technique and threshold for instability are unknown. Purpose: To describe the optimal measurements and thresholds for trochlear dysplasia on magnetic resonance imaging (MRI) that can identify knees with patellar instability in male and female patients. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Knee MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Trochlear dysplasia is a known risk factor for patellar instability in adolescents, and studies have demonstrated abnormalities in the trochlear morphology of patients with patellar instability [1,24,31,32,36]. The bony restraint of the patellofemoral joint formed by the femoral trochlea and the patella is one of the main structures that prevents patellar dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…Trochlear dysplasia is a known risk factor for patellar instability in adolescents, and studies have demonstrated abnormalities in the trochlear morphology of patients with patellar instability [1,24,31,32,36]. The bony restraint of the patellofemoral joint formed by the femoral trochlea and the patella is one of the main structures that prevents patellar dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…That could be due to the fact that, morphologically, the trochleas of female knees are smaller than are those of male knees. However, in a recent study, that difference was not found to be significant after normalization for patient height ( 26 , 27 ) . Therefore, controversy still exists regarding why females are affected more by trochlear dysplasia; that is, whether it is due to the smaller condyle dimensions or to the wider, shallower trochlear groove.…”
Section: Discussionmentioning
confidence: 80%
“…Individuals with bone or muscle anomalies (e.g., trochlear dysplasia or patella alta) have a very unstable patella for which nonsurgical treatment is generally ineffective ( Fig. 1 ) [ 24 , 25 ]. Therefore, surgical intervention is necessary in such cases.…”
Section: Pathognomonic Mechanism Of Patellar Malalignmentmentioning
confidence: 99%
“…The function of the reconstructed MPFL gradually decreases [ 68 ]. Thus, a trochleoplasty is indicated in cases of trochlear dysplasia [ 24 , 25 , 69 ].…”
Section: Surgical Treatment Of Patellar Malalignmentmentioning
confidence: 99%